Preparation and dissolution property of ipriflavone solid dispersion. - Li Ya-ping; Zhang Xian-ying; Zhou Jian-jun; Pei Yuan-ying (Acta Pharmacologica Sinica; Vol 20, No 10 (October 1999): Acta Pharmacologica Sinica, 2016)
AIM: To prepare and identify ipriflavone (IP) solid dispersion, and determine its dissolution property. METHODS: The solvent method was used for preparation and differential scanning calorimetry (DSC), X-ray diffraction and infrared spectrophotometry for identification of IP solid dispersion. The dissolution of the dispersion was determined with paddle method. RESULTS: The dissolution of IP solid dispersion consisting of IP and povidone-k30 (PVP) (1:8) in artificial gastric juice is 6.15 times as high as that of IP alone. The DSC curves, X-ray diffraction patterns and infrared spectrophotometries of IP have been changed obviously by the dispersion. CONCLUSION: The dissolution of IP is increased by solid dispersion method.